The missing ones - Hill, Edwin, 1970- (Hill, Edwin., 1970- Hester Thursby mystery, 2019)
"Hester Thursby has given up using her research skills to trace people who don't want to be found. A traumatic case a few months ago unearthed a string of violent crimes, and left Hester riddled with self-doubt and guilt. Finisterre Island, off the coast of Maine, is ruggedly beautiful and remote - the kind of place tourists love to visit, though rarely for long. But a dilapidated Victorian house has become home to a group of squatters and junkies. A young boy disappeared during the summer, and though he was found safely, the incident stirred suspicion among locals. Now another child is missing. Summoned to the island, Hester discovers a community cleaning up from a devastating storm - and uncovers a murder. Soon Hester begins to connect the crime and the missing children. And as she untangles the secrets at the center of the small community, she finds grudges and loyalties that run deep."--Publisher description.